Predicting extra-musculoskeletal and peripheral manifestations and their role on biologic treatment in patients with axial spondyloarthritis: TReasure experience - Sedat Kiraz; Servet Akar; İhsan Ertenli and Süleyman Serdar Koca and Emine Duygu Ersözlü and Gezmiş Kimyon and Hakan Emmungil and Recep Yılmaz and Askın Ateş and Nilufer Alpay Kanıtez and et al. (Archives of Rheumatology, 2025)
Objectives: This study aimed to examine the frequency and associated factors of extra-musculoskeletal manifestations (EMMs) and peripheral manifestations in an axial spondyloarthritis (axSpA) cohort and their impact on the choice of first biologic treatment. Patients and methods: A total of 1,687 patients with axSpA (978 males, 709 females; mean age: 38.5±11 years) who started their first biologic disease modifying antirheumatic drug (bDMARD) were included from a national prospective database of TReasure between its inception and 2018-2021. Demographic and clinical characteristics, disease-related features, and treatment patterns were compared between patients with and without EMMs or peripheral involvement. Results: Of the patients, 1,283 had radiographic axSpA (r-axSpA), while 404 had nonradiographic axSpA (nr-axSpA). Acute anterior uveitis (AAU) was the most common (11.4%) EMM, and older age, female sex, human leukocyte antigen B27 (HLA-B27) positivity, and a lower Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score were associated with AAU. Female sex, methotrexate use, dactylitis, and higher Ankylosing Spondylitis Disease Activity Score (ASDAS)-serum C-reactive protein (CRP) scores were related to psoriasis (PsO). Inflammatory bowel disease (IBD) and PsO were negatively associated with HLA-B27 positivity. Enthesitis was the most frequent (28.2%) peripheral manifestations, and peripheral arthritis, dactylitis, and enthesitis were independent predictor of each other. In addition, dactylitis and peripheral arthritis were related to more frequent use of conventional disease modifying antirheumatic drugs. In addition, IBD history was associated with less frequent use of etanercept. Older age, less use of sulfasalazine, the absence of enthesitis, and lower Bath Ankylosing Spondylitis Functional Disease Index (BASFI) scores were associated with secukinumab use. Conclusion: Acute anterior uveitis was associated with HLA-B27 positivity, while PsO or IBD were negatively associated with HLA-B27 in patients with axSpA. Peripheral manifestations appeared to be related to each other. Among EMMs, we found that only IBD had an effect on the bDMARD preference.